KEMAMPUAN KOSAKATA BISNIS BAHASA MANDARIN MAHASISWA STBA-PIA SEMESTER VI T.A. 2018/2019 - Rahmatika, Alwiyah; Camila, Tjitra (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
The purpose of this study was to determine the extent to which the level of understanding of business vocabulary in Chinese STBA-PIA students in semester VI T.A. 2018/2019. The researcher used descriptive quantitative research method with saturated sampling technique, and the number of samples was 33 people. The instrument used is a test question. Data collection techniques by giving exams. The test results show that the business vocabulary skills of STBA-PIA students in semester VI T.A. 2018/2019 is categorized as “highly incompetent”. The average score of students is 50.30 and as many as 27 students (82%) are categorized as not passing the exam with a score below 70, and 6 students (18%) are categorized as passing the exam (4 people are quite competent and 2 people are competent). Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana tingkat kemampuan pemahaman kosakata bisnis bahasa Mandarin mahasiswa STBA-PIA semester VI T.A. 2018/2019. Peneliti menggunakan metode penelitian deskriptif kuantitatif dengan teknik sampling jenuh, dan jumlah sampel sebanyak 33 orang. Instrumen yang digunakan adalah soal ujian. Teknik pengumpulan data dengan memberikan ujian. Hasil ujian menunjukkan bahwa kemampuan kosakata bisnis bahasa Mandarin mahasiswa STBA-PIA semester VI T.A. 2018/2019 dikategorikan “sangat tidak kompeten”. Nilai rata-rata mahasiswa adalah 50,30 dan sebanyak 27 orang mahasiswa (82%) dikategorikan tidak lulus ujian dengan nilai di bawah 70, dan 6 orang mahasiswa (18%) dikategorikan lulus ujian (4 orang cukup kompeten dan 2 orang kompeten).